Oxygen separation process using ceramic-based membrane: A review - Fatin Nurwahda, Ahmad; Norazlianie, Sazali; Safwan, Shabi; Nor Hasrul Akhmal, Ngadiman; Mohd Hafiz Dzarfan, Othman (Akademi Baru, 2019)
Membrane technology is known as a cheaper alternative approach that capable to yield high purity oxygen compared to the conventional separation technologies which are pressure swing adsorption (PSA) and cryogenic distillation. The status of advanced ceramic-based membranes in the application of separating oxygen at high temperature is discussed in this paper, including arising issues related to performance in selectivity and separation of membranes. This review paper covers various approaches to solve the problems and issues of the ceramic-based membrane, also, its expected tendency in separating oxygen from the air.